Getting superior Napier grass to dairy farmers in East Africa - WRENmedia (EIARD, 2013)
Napier grass has become the most important fodder crop in Kenya, but 20 years ago head smut disease began to have a devastating impact, turning valuable fodder into thin, shrivelled stems. With the cost of disease control using systemic fungicide beyond the means of most smallholder dairy farmers, KARI began work to select smut-resistant varieties. With access to Napier grass germplasm from ILRI’s genebank, KARI developed two resistant varieties - Kakamega I and Kakamega II. Favourable laboratory results were confirmed in farmer’s fields and work began to multiply planting material. Within a year, cuttings were distributed to over 10,000 smallholder farmers. The new varieties are not quite as productive as the best of Kenya’s local Napier grass varieties, but have still proven popular in smut-affected areas. By 2007, 13 per cent of farmers were using Kakamega I for zero grazing systems in smut prone areas. The chance of head smut resistance breaking down in the new varieties is high, so KARI is screening more materials from ILRI, which is continuing to build its Napier grass collection to have germplasm available to screen for new resistant varieties. In 2012, ILRI provided the Brazilian Agricultural Research Corporation, Embrapa, with Kakamega I and II to enable researchers to use them to develop higher yielding and more nutritious resistant varieties.